Exergy and environmental analysis of black liquor upgrading gasification in an integrated kraft pulp and ammonia production plant. (6th May 2021) - Domingos, Meire Ellen Gorete Ribeiro; Flórez-Orrego, Daniel; Santos, Moisés Teles Dos; Velásquez, Hector Ivan; Junior, Silvio De Oliveira
The black liquor is a byproduct of the kraft pulping process that contains more than half of the exergy content in the total woody biomass fed to the digester, representing a key supply of renewable energy to the pulping process. In this work, the conventional scenario of the black liquor use (i.e., concentration and combustion) is compared with the black liquor upgrading (via) gasification process for ammonia production in terms of economics, exergy efficiency and environmental impact. The combined energy integration and exergy analysis is used to identify the potential improvements that may remain hidden to the energy analysis alone, namely, the determination and mitigation of the process irreversibility. As a result, the exergy efficiencies of the conventional and the integrated cases average 40% and 42%, respectively, whereas the overall emission balance varies from 1.97 to −0.69 tCO2 /tPulp, respectively. The negative CO2 emissions indicate the environmental benefits of the proposed integrated process compared to the conventional kraft pulp mill.